Islamic Republic of Iran : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2014)
This staff report for the 2014 Article IV Consultation on the Islamic Republic of Iran focuses on economic developments and policies. The IMF report had achieved considerable progress in raising per capita income and living standards. Large shocks and weak macroeconomic management have had a significant impact on macroeconomic stability and growth. The external environment remains uncertain and delaying domestic reforms raise the risk of entrenching the economy in a low-growth and high-inflation scenario, underscoring the need to address long-standing weaknesses in the policy framework and the economy.